Risk factors for recurrent severe anemia among previously transfused children in Uganda: an age-matched case-control study - Aggrey Dhabangi; Richard Idro; Chandy C. John; Walter H. Dzik; Robert Opoka; Ronald Ssenyonga; Michael Boele van Hensbroek (BMC Pediatrics, 2019)
Abstract Background In resource-poor settings, transfused children often experience recurrence of severe anemia (SA) following discharge from hospital. This study determined the factors associated with recurrent severe anemia (RSA) among previously transfused Ugandan children aged less than 5 years. Methods A case-control study was conducted in five hospitals in Uganda from March 2017 to September 2018. We prospectively enrolled 196 hospitalised children who had been transfused for severe anemia 2 weeks to 6 months prior to enrollment. Of these, 101 children (cases) were re-admitted with a hemoglobin [Hb] level of ≤6 g/dL and required transfusion; and 95 children (age-matched controls) were admitted for other clinical illness with a Hb > 6 g/dL. Children known to have sickle cell anemia, cancer, or bleeding disorders were excluded. Clinical and laboratory evaluation were done. Conditional logistic regression adjusted for age, was used to determine factors associated with RSA. Results The median time (IQR) between the earlier transfusion and enrollment was 3.5 (1.9–5.7) months for cases, and was 5.0 (2.9–6.0) months for controls (p-value = 0.015). Risk factors (adjusted odds ratio, 95% confidence interval, and significance) for development of RSA were: hemoglobinuria (36.33, 2.19–600.66, p = 0.012); sickle cell anemia – newly diagnosed (20.26, 2.33–176.37, p = 0.006); history of earlier previous transfusions (6.95, 1.36–35.61, p = 0.020) and malaria infection (6.47, 1.17–35.70, p = 0.032). Conclusion Malaria chemoprevention, follow up visit for Hb check after discharge from hospital and sickle cell screening among previously transfused children represent practical strategies to prevent and identify children at risk for recurrent severe anemia. The cause of hemoglobinuria in children merits further investigations.